OPTIMALISASI PEMANFAATAN PERPUSTAKAAN FAKULTAS ILMU TARBIYAH DAN KEGURUAN (FITK) UIN MAULANA MALIK IBRAHIM MALANG SEBAGAI REFERENSI TEORI DAN KEPUSTAKAAN DALAM KEGIATAN PENELITIAN DAN PENULISAN KARYA ILMIAH MAHASISWA - Fitriah, Nurlaeli (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Optimizing the use of the library of FITK UIN Maulana Malik Ibrahim Malang as a reference of theory in research and academic writing of students. Research Report. Malang: Tarbiyah Faculty of UIN Maulana Malik Ibrahim Malang, 2016. This research aimed to determine the extent of FITK UIN Maulana Malik Ibrahim Malang students in utilization of library in faculty and optimal uses of the library as a resource of references to explore the theory and literature references to support the research and writing of scientific papers. This survey studies using a quantitative approach of research. The research survey was conducted to determine how far the use of the library by students. Then the results of the survey are used to describe the optimization of the use of the library by student in Tarbiyah Faculty UIN Maulana Malik Ibrahim Malang for finding sources and theoretical reference for research and writing of scientific papers. The results of the study are as follows : 1 ) utilization of the library faculty by students in learning center function by 77.8 % , amounting to 46.4 % for studying center fuction , research center at 40.8 % , information resources center amounted to54.7 % , preservation of knowledge center at 56.3 % and the dissemination of information centers at 28.6 % ; 2 ) optimizing the use of the library by students indicated byÂ the percentage of the library functions that are considered dominant. they are learning center, information resources center and the preservation of knowledge center. It also indicated by students' understanding of the existence of the library of faculty which amounted to 94.30 % and by the library activity of the students, on the beginning as a student which amounted to48.2 % and then on the continued to the present as a student at 64.2 %.Â Keywords: Optimalize of Library, The Use of Library